Pulmonary Tuberculosis Relapse - Putu Parmi Asih (Faculty of Medicine, Public Health, and Nursing, 2020)
The patient is a 27-year-old married male, who does not work. Since contracting the tuberculosis (TB) illness, the patient complained of feeling tired and weak so he decided to stop working. The patient usually feels that rest helps the healing process of the pain and by not working, they feel more focused on the treatment of the disease because it requires them to go to the Puskesmas every day to get treatment. The patient’s wife works as a rice trade worker. The patient has a 3.5-year-old daughter. The patient originally came from the Karangasem Regency, Tulamben, which is included in the red zone of the eruption of Mount Agung. So actually, this patient is a refugee. But he did not complete the documents as a refugee, so the patient did not get the recognized rights as a refugee like getting free medical treatment. The patient who does not have the Indonesia Health Card/Kartu Indonesia Sehat (KIS) is considered to not have any health insurance and is included in the lowest economic status.